On the phenomenon or Arias-Stella reaction - Muñóz Torcello, Carlos (2015)
The author defends the originality of the work of Dr. Arias-Stella in relation to the histological changes that have been designated in the literature as "Arias-Stella reaction". Also it indicates that the merit of the Peruvian researcher was first described endometrial alterations associated with pregnancy.